2015
DOI: 10.1007/s11745-015-4017-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined PCSK9 and APOE Polymorphisms are Genetic Risk Factors Associated with Elevated Plasma Lipid Levels in a Thai Population

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) and apolipoprotein E (ApoE) play a key role in the regulation of lipid metabolism. We aimed to investigate the effects of PCSK9 (R46L, I474V, and E670G) and APOE polymorphisms on lipid levels in a Southern Thai population. A total of 495 participants (307 urban, 188 rural) were recruited for the study. Anthropometric and biochemical variables were evaluated. PCSK9 and APOE polymorphisms were analyzed using PCR-RFLP. The 46L urban male carriers had significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
3
13
3
Order By: Relevance
“…In addition, the frequency of PCSK9 474V allele was 1.78% in this study. Our finding was similar to a previous report in the Thai population (1.86%) . However, the higher frequency of 474V allele has been observed in Japanese (2.48%), Brazilian (19.10%‐21.6%), African Canadian (19.40%), and African American (22%) populations.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, the frequency of PCSK9 474V allele was 1.78% in this study. Our finding was similar to a previous report in the Thai population (1.86%) . However, the higher frequency of 474V allele has been observed in Japanese (2.48%), Brazilian (19.10%‐21.6%), African Canadian (19.40%), and African American (22%) populations.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have also reported that E4 allele is generally associated with increased plasma cholesterol and LDL‐C, and E2 allele is associated with decreased plasma cholesterol and LDL‐C compared with the E3 allele . The allele frequencies of the APOE polymorphisms (E2 7.11%, E3 79.56%, E4 13.33%) in this study were similar to previous reports among the Thai population (E2 7.18%‐10.42%, E3 77.04%‐77.51%, E4 12.54%‐15.43%) . APOE4 allele in our study was higher than Japanese (10.5%), Han Chinese (7.5%), Taiwanese (7.5%), and Korean (9%) populations but lower than the Malaysian population (20.20%) .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations